PELATIHAN BUDIDAYA LEBAH TRIGONA DENGAN TEKNIK BELAH KOLONI DAN PENGENALAN BENTUK STUP DI DESA ROMPEGADING KABUPATEN MAROS - Sitti Nuraeni; Budirman Bahtiar; Andi Detti Yunianti; Budiaman Budiaman; Siti Halimah Larekeng; Andi Prastiyo; Nurfadilah Latif; Marwan Rajab; Gilang Ramadhan; Rehan Rehan (Bajang Institute, 2022)
Stingless bees have different local names but are more commonly known as trigona bees. One of the efforts to increase the productivity of trigona bees from their cultivation is colony propagation. The purpose of this community service is to provide training to multiply trigona bee colonies with colony splitting techniques and the introduction of several forms hive of bee. The activity was carried out in the form of a workshop which was attended by two groups of trigona beekeepers. Based on the results of the evaluation through a questionnaire, the training succeeded in increasing the knowledge of participants about the propagation and introduction of the hive form of the trigona bee colony. As a follow-up to this activity, they conducted mentoring activities for trigona beekeeper groups in Rompegading Village, Cenrana District, Maros Regency. Continuous training and mentoring programs will be able to better understand and accelerate independent trigona cultivation groups in managing their meliponiary. Increased income for breeders as direct beneficiaries of meliponiculture.